A sea in flames : the Deepwater Horizon Oil blowout / Carl Safina. - Safina, Carl, 1955- (Crown Publishers, 2011)
"The first book about the BP disaster by a world-renowned oceanographer, A SEA IN FLAMES examines the environmental and social consequences of the spill from the perspective of those directly affected by it. It will be published on the one-year anniversary of the spill, in April 2011. The Gulf of Mexico oil spill is among the greatest environmental catastrophes in U.S. history. Carl Safina's Blowout provides an extraordinary perspective on it. Consisting of three parts, it reveals and details: this shocking manmade environmental disaster, its occurrence with respect to the oil industry's and the government's complete inability to adequately respond, and the inevitable environmental effects. By telling the stories of three working families, Safina goes behind the scenes with fishermen, oystermen, and oilmen whose lives--and habitats--have been irreparably changed. But will energy and environmental policy change as well? Safina addresses these issues in a rich, deeply personal investigation of a catastrophe he has reported--and blogged on--from the beginning"--Provided by publisher.